Error Analysis in The Travel Writing Made by The Students of English Study Program - Agustina, Vika; Junining, Esti (JEELS (Journal of English Education and Linguistics Studies), 2015)
This study was conducted to identify the kinds of errors in surface strategy taxonomy and to know the dominant type of errors made by the fifth semester students of English Department of one State University in Malang-Indonesia in producing their travel writing. The type of research of this study is document analysis since it analyses written materials, in this case travel writing texts. The analysis finds that the grammatical errors made by the students based on surface strategy taxonomy theory consist of four types. They are (1) omission, (2) addition, (3) misformation and (4) misordering. The most frequent errors occuring in misformation are in the use of tense form. Secondly, the errors are in omission of noun/verb inflection. The next error, there are many clauses that contain unnecessaryphrase added there.